ANALISIS INFORMASI TIGA DIMENSI DALAM KESELAMATAN PENERBANGAN DAERAH PERKOTAAN - Sugito, Nanin Trianawati (Indonesia University of Education, 2010)
Safety of flight is very related to the factors of air transportation infrastructure is the airport. One of the measures to minimize the occurrence of the accident airplane and the possibility to fall in residential areas because the location of the airport and fly the aircraft trajectory relative to urban areas is the existence of a regulation called is Flight Operations Safety Area. The function of Flight Operations Safety Area is adjusting the height of buildings or objects grow both fixed and which can move (mobile) to no higher than the permitted height limit. Flight Operations Safety Area is a virtual surface (imaginary surface) with the provisions of height, length (distance) or radius, and angle of slope or widening a distinct difference for each surface area. Flight Operations Safety Area formation in 3-dimensional object is appropriate to produce cutting-edge information about the list of objects that become an obstacle (obstacle). This information include by regarding obstacle height that exceeds the provisions in each region Flight Operations Safety Area for the sake of flight safety. In this study focuses on the study of the formation of 3-dimensional information Flight Operations Safety Area urban airports in support of security and safety of aircraft in terms of determining the legal basis Flight Operations Safety Area in organizing the flight. Very important Flight Operations Safety Area applied to airports located in urban areas. Because most land use in areas Flight Operations Safety Area in urban areas are housing, the height of buildings in the area of absolute Flight Operations Safety Area note to support aviation safety. Flight Operations Safety Area generated 3-dimensional expected to provide solution in analyze the height of buildings around the airport to support aviation safety.